Decolonization and Restitution: Moving Towards a More Holistic and Relational Approach: Report on the Panel on Ethnographic Museums and Indigenous People, ICOM Kyoto, September 2019. Issue 1 (1st July 2020) - Rivet, Michèle
Abstract : At the twenty-fifth triennial ICOM International General Conference, which took place in Kyoto, Japan, on 1 to 7 September 2019, decolonization and restitution were discussed during a whole afternoon under the heading "Decolonization and Restitution: Moving Towards a More Holistic Perspective and Relational Approach." Two consecutive sessions with simultaneous translation in English, French, Spanish, and Japanese were attended by almost one thousand people in each session. Speakers for both sessions were representatives of their respective ICOM National Committees. ICOM's Code of Ethics for Museums, adopted in 1986 at the fifteenth General Conference in Buenos Aires, is recognized worldwide and serves as a guideline in museum work, especially the sixth principle: "Museums work closely with both the communities from which their collections originate and those they serve."